Gender diversity in autistic clients: an ethical perspective - Glaves, Katie Jo; Kolman, Leah (Frontiers in Psychiatry, 2023)
Autism and gender dysphoria commonly co-occur, however, it can be difficult to find clinicians who are comfortable affirming clients who are transgender/gender non-conforming (TNGC) and autistic; this difficulty stigmatizes clients and causes harm to their mental health. Yet clinicians have an ethical imperative to respect the autonomy and dignity of all clients, including those who are autistic and TNGC. This paper discusses the ethical duties of clinicians to affirm autistic, TGNC clients, using empirical literature.